2008
DOI: 10.1002/pssa.200723192
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of chlorine‐doped ZnO thin films grown by MOCVD

Abstract: Chlorine‐doped ZnO thin films were grown by MOCVD on sapphire and fused silica. Chlorine is incorporated in substitution for oxygen and acts as a donor, leading to an increase of electron concentration. Transport properties were studied for samples with different chlorine content. Hall effect measurements show the increase of electron carrier concentration and decrease of electron mobility on increasing the amount of chlorine incorporated in ZnO. Carrier concentrations as high as 6.5 × 1020 cm–3 has been achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…[1,2] ZnO is one of the most suitable materials for the photocatalytic process under illumination with ultraviolet light;t he typical electronm obility in ZnO is 10-100 times higher than that in TiO 2 ,w hich leads to ar educed electricalr esistance and enhanced electron transfer efficiency. [3] ZnO can be prepared through severalc hemical and physical methods such as sol-gel methods, [4,5] ultrasonic spray pyrolysis, [6] metal organic chemical vapor deposition, [7,8] pulsed laser deposition, [9,10] and sputtering methods. [11][12][13] Among them, reactive sputtering deposition has shown more advantages including control of the preferred crystalline orientation, growth atarelatively low temperature, no need for post-calcination, good interfacial adhesion to the substrate, and ah igh packing density of the grown film.…”
mentioning
confidence: 99%
“…[1,2] ZnO is one of the most suitable materials for the photocatalytic process under illumination with ultraviolet light;t he typical electronm obility in ZnO is 10-100 times higher than that in TiO 2 ,w hich leads to ar educed electricalr esistance and enhanced electron transfer efficiency. [3] ZnO can be prepared through severalc hemical and physical methods such as sol-gel methods, [4,5] ultrasonic spray pyrolysis, [6] metal organic chemical vapor deposition, [7,8] pulsed laser deposition, [9,10] and sputtering methods. [11][12][13] Among them, reactive sputtering deposition has shown more advantages including control of the preferred crystalline orientation, growth atarelatively low temperature, no need for post-calcination, good interfacial adhesion to the substrate, and ah igh packing density of the grown film.…”
mentioning
confidence: 99%
“…The Cl-doped ZnO lms prepared in this work have electrical resistivity in the same order of magnitude comparing to those obtained using atomic layer deposition (0.55 at% Cl-doped ZnO lms: r ¼ 1.215 Â 10 À2 U cm, n ¼ 5.901 Â 10 19 cm À3 and m ¼ 31.81 cm 2 V À1 s À1 ) 32 and metal-organic CVD (r ¼ 3.6 Â 10 À2 U cm, n $ 10 20 cm À3 and m ¼ 9-14 cm 2 V À1 s À1 ), 31,34 but higher than that prepared by physical layer deposition (2.4 at% Cldoped ZnO lms: r ¼ 6.344 Â 10 À4 U cm, n ¼ 4.04 Â 10 20 cm À3 and m ¼ 23.75 cm 2 V À1 s À1 ). 30,33 Computational studies have previously revealed that oxygen vacancy is the donor-type defect which show the lowest formation energy under n-type conditions; therefore it may also be valuable to take oxygen deciency into an account for the conductivity in ZnO lm prepared under an inert atmosphere like N 2 .…”
Section: Transparent Conducting Oxide (Tco) Propertiesmentioning
confidence: 99%
“…However, there have been some reports on the electrical, optical and photoelectrochemical properties of Cl-doped ZnO, which show the potential of Cl doping. [30][31][32][33][34][35] Therefore, we were interested in exploring further the novel properties of ZnO:Cl, in particular the lm deposition method which has been shown to play a key role in modifying the lm properties. Aerosol-assisted chemical vapour deposition (AACVD) is an effective technique to control the morphology and simultaneously the properties of the deposited lms.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike trivalent cation, doping with anion has always received less attention and thus it is much less discussed. Some anions like F, Cl have been reported to improve the conductivity of ZnO film [36][37][38][39][40]. The reports on anionic dopant F are very few as compared to that of metallic cationic dopants although it is also attractive because substitution of O by F is known to perturb the valence band mostly, leaving the conduction band relatively free of scattering.…”
Section: Introductionmentioning
confidence: 99%